2013
DOI: 10.1109/tsmca.2012.2221038
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Springs With Visual and Proprioceptive Motion Cues: Implications for Prosthetics

Abstract: Manipulating objects with an upper limb prosthesis requires significantly more visual attention than doing the same task with an intact limb. Prior work and comments from individuals lacking proprioception indicate that conveying prosthesis motion through a nonvisual sensory channel would reduce and possibly remove the need to watch the prosthesis. To motivate the design of suitable sensory substitution devices, this study investigates the difference between seeing a virtual prosthetic limb move and feeling on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…Gurari and colleagues [30] showed that one need not overload the visual channel to provide proprioceptive information. They describe a novel experimental apparatus that mimics the usage of a myoelectrically controlled upper limb prosthesis in a one-DOF rotational spring discrimination task.…”
Section: B Haptic Technologiesmentioning
confidence: 99%
“…Gurari and colleagues [30] showed that one need not overload the visual channel to provide proprioceptive information. They describe a novel experimental apparatus that mimics the usage of a myoelectrically controlled upper limb prosthesis in a one-DOF rotational spring discrimination task.…”
Section: B Haptic Technologiesmentioning
confidence: 99%
“…More details about the study can be found in Gurari et al (2013). The motivation for this work was to investigate whether the upper-limb prosthesis experience can be improved by reducing the demand on vision during arm control.…”
Section: Experiment: Role Of Motion Cues In Compliance Perceptionmentioning
confidence: 99%
“…Tan et al (1992) showed that springs can be discriminated based on force cues, The mean WF and PSE values exclude Participants 5, 7, and 9, since a goodness-of-fit was not achieved for one sensory condition for each of these participants, as indicated by the asterisk (*). Adapted from Table 10.1 in Gurari et al (2013) © IEEE 2013 Across all trials in each testing condition during the exploration of a standard spring for a representative participant, the respective minimum, lower quartile, median, upper quartile, and maximum distance that the finger traveled is given. Adapted from Table IV in Gurari et al (2013) © IEEE 2013 not compliance cues, if the distance one's hand travels does not vary across testing trials, giving WFs close to 0.08.…”
Section: Mle Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The proprioceptive sense is significantly more useful than visual positioning when controlling a prosthetic arm. However, there are no current proprioceptive feedback devices commercially available for use in prosthetic arms [25].…”
Section: Novel Haptic Feedback Researchmentioning
confidence: 99%